Vicenistatin induces early endosome-derived vacuole formation in mammalian cells. Issue 5 (3rd May 2016) - Nishiyama, Yuko; Ohmichi, Tomohiro; Kazami, Sayaka; Iwasaki, Hiroki; Mano, Kousuke; Nagumo, Yoko; Kudo, Fumitaka; Ichikawa, Sosaku; Iwabuchi, Yoshiharu; Kanoh, Naoki; Eguchi, Tadashi; Osada, Hiroyuki; et al.
Abstract: Homotypic fusion of early endosomes is important for efficient protein trafficking and sorting. The key controller of this process is Rab5 which regulates several effectors and PtdInsPs levels, but whose mechanisms are largely unknown. Here, we report that vicenistatin, a natural product, enhanced homotypic fusion of early endosomes and induced the formation of large vacuole-like structures in mammalian cells. Unlike YM201636, another early endosome vacuolating compound, vicenistatin did not inhibit PIKfyve activity in vitro but activated Rab5-PAS pathway in cells. Furthermore, vicenistatin increased the membrane surface fluidity of cholesterol-containing liposomes in vitro, and cholesterol deprivation from the plasma membrane stimulated vicenistatin-induced vacuolation in cells. These results suggest that vicenistatin is a novel compound that induces the formation of vacuole-like structures by activating Rab5-PAS pathway and increasing membrane fluidity. Graphical abstract: : Vicenistatin is a novel compound that induces the formation of vacuole-like structures by activating Rab5-PAS pathway and increasing membrane fluidity.